Improving Quality of Care in Primary Health-Care Facilities in Rural Nigeria - Okoli Ugo; Eze-Ajoku Ezinne; Oludipe Modupe; Spieker Nicole; Ekezie Winifred; Ohiri Kelechi (SAGE Publishing, 2016)
Background: Nigeria has a high population density but a weak health-care system. To improve the quality of care, 3 organizations carried out a quality improvement pilot intervention at the primary health-care level in selected rural areas. Objective: To assess the change in quality of care in primary health-care facilities in rural Nigeria following the provision of technical governance support and to document the successes and challenges encountered. Method: A total of 6 states were selected across the 6 geopolitical zones of the country. However, assessments were carried out in 40 facilities in only 5 states. Selection was based on location, coverage, and minimum services offered. The facilities were divided randomly into 2 groups. The treatment group received quality-of-care assessment, continuous feedback, and improvement support, whereas the control group received quality assessment and no other support. Data were collected using the SafeCare Healthcare Standards and managed on the SafeCare Data Management System-AfriDB. Eight core areas were assessed at baseline and end line, and compliance to quality health-care standards was compared. Result: Outcomes from 40 facilities were accepted and analyzed. Overall scores increased in the treatment facilities compared to the control facilities, with strong evidence of improvement ( t = 5.28, P = .0004) and 11% average improvement, but no clear pattern of improvement emerged in the control group. Conclusion: The study demonstrated governance support and active community involvement offered potential for quality improvement in primary health-care facilities.